Ecologie degli ambienti urbani: sfide applicative - Pozzi, Giacomo; Rimoldi, Luca; Tosi Cambini, Sabrina (Antropologia Pubblica, 2025)
Following the path that the Urban Environment Lab – UrbE-Lab – Antropologia applicata agli ambienti urbani, a permanent laboratory of the Italian Society of Applied Anthropology, has been following since its foundation, the contribution proposes a reflection on contemporary urban anthropology in the light of its applicative uses in the national and international sphere. In particular, the article focuses on the notion of the urban environment, understood as an essential axis for the articulation of a relational and applied anthropology. The first part of the article reconstructs the historical and intellectual context that led Italian contemporary urban anthropology to adopt an applied approach. The second part discusses in detail the theoretical approaches, themes, methodologies and perspectives that characterise the work of UrbE-Lab. The third part, based on a dialogue with the contributions in this dossier, discusses some theoretical and ethnographic proposals for articulating the notion of the urban environment in the contemporary world, always in the light of its applicative and public repercussions.